The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/iwj.12592
|View full text |Cite
|
Sign up to set email alerts
|

Healing enhancement of diabetic wounds by locally infiltrated epidermal growth factor is associated with systemic oxidative stress reduction

Abstract: The diabetic foot ulcer (DFU) is the leading cause of lower extremity amputation worldwide and is directly associated with comorbidity, disability and mortality. Oxidative stress mechanisms have been implicated in the pathogenesis of these wounds. Intra-lesional infiltration of epidermal growth factor has emerged as a potential therapeutic alternative to allow for physiological benefit while avoiding the proteolytic environment at the centre of the wound. The aim of this study was to characterise the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 60 publications
4
34
0
4
Order By: Relevance
“…Diabetes is a multifactorial toxic entity in which glucotoxicity is associated with increased reactive oxygen species levels, disruption of the balance between pro‐degradative an pro‐synthetic forces, as to the AGE/RAGE noxious impact, thus leading to cellular proliferative and survival reserves demise . In line with this, our group had previously demonstrated that ulcerated diabetic subjects behave as a particular diseased group, as they exhibit an exacerbation of the oxidative stress arm as compared with non‐ulcerated diabetics . Here, we confirm that nine EGF infiltrations over 3 weeks were sufficient to reduce the circulating levels of oxidative reactants although with no effect on the circulating antioxidant defence reserves.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Diabetes is a multifactorial toxic entity in which glucotoxicity is associated with increased reactive oxygen species levels, disruption of the balance between pro‐degradative an pro‐synthetic forces, as to the AGE/RAGE noxious impact, thus leading to cellular proliferative and survival reserves demise . In line with this, our group had previously demonstrated that ulcerated diabetic subjects behave as a particular diseased group, as they exhibit an exacerbation of the oxidative stress arm as compared with non‐ulcerated diabetics . Here, we confirm that nine EGF infiltrations over 3 weeks were sufficient to reduce the circulating levels of oxidative reactants although with no effect on the circulating antioxidant defence reserves.…”
Section: Discussionsupporting
confidence: 86%
“…The present study validates previous observations of our group, demonstrating the systemic impact of locally infiltrated EGF in reestablishing a pro‐physiological redox balance. Furthermore, here we show that EGF pharmacodynamic bounties also encompass the attenuation of endovascular pro‐inflammatory markers with dramatic negative impact in diabetic individuals' general homeostasis.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…A number of studies have shown that (1113) VSD treatment can effectively shorten wound healing time, reduce the pain associated with wound dressing changes, and effectively avoid cross infection. VSD is performed in a closed system, and the negative pressure drainage system promptly removes any exudates and necrotic tissue to achieve zero necrotic tissue accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-lesional infiltration of epidermal growth factor (EGF) has emerged as a potential therapeutic alternative to allow for physiological benefit while avoiding the proteolytic environment at the centre of the wound. Intra-lesional administration of EGF was associated with a significant recovery of oxidative stress and antioxidant reserve markers leading the authors to conclude that epidermal growth factor intra-ulcer therapy contributes to restore systemic redox balance in patients with DFUs (96). Furthermore, intralesional insulin injection in DFU showed promising results in terms of wound healing (97).…”
Section: Accepted Manuscriptmentioning
confidence: 99%